History of the formation and development of Kazakhstan's conducting art - Amze, Mussilim; Bultbayeva Aizada, Tatkenova Sholpan, Sabirova Aliya, (Opción, 2019)
The aim of the research is to study and explore features of the historical formation of the Kazakh conducting art complexly via methodical manuals, written on the basis of the conductor's pedagogical experience, which could be used at all branches of the conductor's art. As a result, the leaders of the symphony orchestra of the Dzhambul Philharmonic Society were the brightest representatives of the Kazakh conducting art, whose names will remain forever in the history of the musical culture of our republic. In conclusion, a specialist must know the vital and creative paths of prominent representatives of culture